2022
DOI: 10.7769/gesec.v13i3.1345
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativas de crédito e desenvolvimento local

Abstract: Buscou-se com este artigo mapear a produção científica a respeito das cooperativas de créditos, nas diversas áreas de estudo, presentes nas bases de dados Elsevier’s Scopus e Web of Science (WoS). Utilizou-se o Excel e o RStudio para realizar a análise bibliométrica dos 1365 artigos publicados em 730 fontes recuperados desde 1911. Analisou-se a evolução do número de artigos publicados a respeito das cooperativas de crédito, os periódicos mais relevantes e os autores mais produtivos e citados. Fez-se ainda uma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…In this research, as shown in Table 8, large effects were found for the constructs of management effectiveness, strategic planning, and work processes. This management effectiveness in universities contributes to local development [25]. Continuing, as this research deals with correlations and linear regressions, we must evaluate whether these relationships are significant (p-value less than or equal to 0.05), since for the cases of correlation it is established the null hypothesis (H0) as r = 0 and for regression cases, it is established with H0: Γ = 0 (path coefficient = 0).…”
Section: Structural Equation Model Analysismentioning
confidence: 99%
“…In this research, as shown in Table 8, large effects were found for the constructs of management effectiveness, strategic planning, and work processes. This management effectiveness in universities contributes to local development [25]. Continuing, as this research deals with correlations and linear regressions, we must evaluate whether these relationships are significant (p-value less than or equal to 0.05), since for the cases of correlation it is established the null hypothesis (H0) as r = 0 and for regression cases, it is established with H0: Γ = 0 (path coefficient = 0).…”
Section: Structural Equation Model Analysismentioning
confidence: 99%
“…Este estudio se justifica porque las cooperativas de crédito representan una importancia nacional e internacional, ya que promueve la aplicación de recursos privados y asume riesgos a favor de la comunidad donde se inserta. En Brasil, el sistema de crédito cooperativo comprende aproximadamente 14 millones de cooperativistas y este número aumenta gradualmente cada año (Queiroz, Flach & Mattos, 2022). Así, este estudio contribuye teórica y empíricamente ampliando la literatura sobre el uso de SCG (Aguiar & Frezatti, 2007;Oyadomari, 2008), así como con la necesidad de desarrollar una estructura adecuada de performance management and control (en adelante, PMC), ya que se encuentra en sus primeras etapas (Berry et al, 2009).…”
Section: Introductionunclassified